Predicting the shifts of absorption maxima of azulene derivatives using molecular modeling and ZINDO CI calculations of UV-vis spectra - Patalinghug, Wyona C. (Animo Repository, 2007)
This activity enables the students to qualitatively predict whether a substituent will cause a blue or red shift of the absorption peaks of azulene based on frontier molecular orbital shapes, although it does not quantitatively predict the magnitude of the shifts. Moreover, it allows the students to verify their predictions using computational chemistry, specifically ZINDO CI, which calculates the LTV-vis spectra of the azulene derivatives. The variations in the HOMO-LUMO and HOMO-LUMO+1 gaps can be plotted to further corroborate the predictions.